Politics of the French empire in the east Adriatic coast (1809–1814) - Prekic, Adnan (Balcanica Posnaniensia. Acta et studia, 2024)
The article processes the period of the French Empire’s rule on the east Adriatic coast between 1809 and 1814. Based on the relevant literature and historical sources, the article points to events that followed Campo Formio's peace in 1797 until the destruction of French rule in 1814. Special focus is placed on the activities of the new rulers, based on the ideas of the French revolutions, which sought to transform the area of east Adriatic and integrate it into the state system of the French empire, with the goal of creating a united political, administrative, militaristic, economic and cultural-educational area. In that context, in the article, the main question being examined is the formation of the Illyrian provinces, which were intended to be a separate province of the French empire, which was supposed to unite different national and religious communities that spoke the same language. With a comprehensive analysis of political and social changes, an attempt is made to point to a pioneer attempt to transform a patriarchal and traditional community, through the implementation of modern models of public administration, healthcare, and education.